Lipid Rafts in Mast Cell Biology. (3rd January 2011) - Silveira e Souza, Adriana Maria Mariano; Mazucato, Vivian Marino; Jamur, Maria Célia; Oliver, Constance
Abstract : Mast cells have long been recognized to have a direct and critical role in allergic and inflammatory reactions. In allergic diseases, these cells exert both local and systemic responses, including allergic rhinitis and anaphylaxis. Mast cell mediators are also related to many chronic inflammatory conditions. Besides the roles in pathological conditions, the biological functions of mast cells include roles in innate immunity, involvement in host defense mechanisms against parasites, immunomodulation of the immune system, tissue repair, and angiogenesis. Despite their growing significance in physiological and pathological conditions, much still remains to be learned about mast cell biology. This paper presents evidence that lipid rafts or raft components modulate many of the biological processes in mast cells, such as degranulation and endocytosis, play a role in mast cell development and recruitment, and contribute to the overall preservation of mast cell structure and organization.